Table of contents and editorial information - R. E. Stevenson (Journal of Applied Communications, 1970)
Editorial front matter and table of contents for vol. 53, no. 4 (Oct.-Dec. 1970) of ACE, the official journal of the American Association of Agricultural College Editors.